Adobe After Effects classroom in a book 2020 : the official training workbook from Adobe - Gyncild, Brie; Fridsma, Lisa (Classroom in a book., 2020)
Adobe After Effects Classroom in a Book (2020 release) is the best-selling guide to Adobe's powerful motion graphics program. The 15 project-based lessons in this book teach students step-by-step the key techniques for working efficiently in After Effects and delivering in the widest possible range of media types. In addition to the key elements of the After Effects interface, this revised edition covers new features and techniques. Learn how to create, manipulate, and optimize motion graphics for film, video, DVD, the web, and mobile devices. Gain hands-on experience animating text and images, customizing a wide range of effects, tracking and syncing content, rotoscoping, removing unwanted objects, and correcting color. Learn to create 3D content with both After Effects and Maxon Cinema 4D Lite (included with the software). The online companion files include all the necessary assets for readers to complete the projects featured in each chapter. All buyers of the book get full access to the Web Edition: A Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.